Evaluation of hotel service-performance process in Bulgaria - Georgina Lukanova (UTMS Journal of Economics, 2010)
The paper analyses the hotel service-performance process in Bulgarian hotels, which is based on the results of the research about tourists' opinion on basic moments in service process. One of the most important characteristics of hotel industry is the leading role of the human factor in service-performance process. It cannot be accomplished without the participation of the customer and without the participation of the staff. This makes the evaluation of service process strongly subjective. Because of this, customer needs satisfaction is a big challenge for the hotel management. Under the present conditions of an increased competition, satisfying customers means offering service- performance process, which not only meets, but also exceeds guests' expectations. This can be achieved by a preliminary study of their requirements and expectations.
Keywords: 330; hotel industry; hotel service operations; service-performance process; satisfaction from service